Comparative efficacy of two interventions to discontinue long-term benzodiazepine use: cluster randomised controlled trial in primary care. (June 2014) - Vicens, Caterina; Bejarano, Ferran; Sempere, Ermengol; Mateu, Catalina; Fiol, Francisca; Socias, Isabel; Aragonès, Enric; Palop, Vicente; Beltran, Jose Luis; Piñol, Josep Lluís; Lera, Guillem; Folch, Silvia; et al.
Abstract : Background: Benzodiazepines are extensively used in primary care, but their long-term use is associated with adverse health outcomes and dependence. Aims: To analyse the efficacy of two structured interventions in primary care to enable patients to discontinue long-term benzodiazepine use. Method: A multicentre three-arm cluster randomised controlled trial was conducted, with randomisation at general practitioner level (trial registration ISRCTN13024375). A total of 532 patients taking benzodiazepines for at least 6 months participated. After all patients were included, general practitioners were randomly allocated (1:1:1) to usual care, a structured intervention with follow-up visits (SIF) or a structured intervention with written instructions (SIW). The primary end-point was the last month self-declared benzodiazepine discontinuation confirmed by prescription claims at 12 months. Results: At 12 months, 76 of 168 (45%) patients in the SIW group and 86 of 191 (45%) in the SIF group had discontinued benzodiazepine use compared with 26 of 173 (15%) in the control group. After adjusting by cluster, the relative risks for benzodiazepine discontinuation were 3.01 (95% CI 2.03–4.46, P <0.0001) in the SIW and 3.00 (95% CI 2.04–4.40, P <0.0001) in the SIF group. The most frequently reported withdrawal symptoms were insomnia, anxiety and irritability. Conclusions: Both interventions led to significant reductions in long-term benzodiazepine use in patients without severe comorbidity. A structured intervention with a written individualised stepped-dose reduction is less time-consuming and as effective in primary care as a more complex intervention involving follow-up visits.